2022
DOI: 10.1002/jcla.24359
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome: New biomarkers in early screening of colorectal cancer

Abstract: Background Certain “star intestinal bacteria” have been found to act as a contributor to the development of colorectal cancer (CRC). Besides, given that the gut microbiome can be detected in a diverse range of samples (stool, tissue, blood, etc), it is categorized into fecal microbiome, blood microbiome, and tissue microbiome. Methods To provide an overview of the recent research progress, this review summarizes the characteristics of the gut microbiome in different samples at each stage of CRC and their scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(98 reference statements)
3
14
0
Order By: Relevance
“…Following these genes are two major clusters one containing genes at the decisive level for the BRCA, OV, and CL mechanistic models, and one containing genes at the decisive level for all three TCGA cancers. The consistent nature of functional evidence across this gene set is in agreement with findings from past investigations - multiple studies have indicated the prognostic value of members of this pathway in gynecological cancers - including breast, 35 ovarian, 36 and endometrial 37 cancer. The second-highest gene set in the KEGG analyses is the adherens junction gene set (p-value = 5.52 × 10 −5 ) (Figure 2b).…”
Section: Resultssupporting
confidence: 89%
“…Following these genes are two major clusters one containing genes at the decisive level for the BRCA, OV, and CL mechanistic models, and one containing genes at the decisive level for all three TCGA cancers. The consistent nature of functional evidence across this gene set is in agreement with findings from past investigations - multiple studies have indicated the prognostic value of members of this pathway in gynecological cancers - including breast, 35 ovarian, 36 and endometrial 37 cancer. The second-highest gene set in the KEGG analyses is the adherens junction gene set (p-value = 5.52 × 10 −5 ) (Figure 2b).…”
Section: Resultssupporting
confidence: 89%
“…Some OTUs with relatively high importance scores were noticeably clustered together in local regions. Figure S7 provides an example of a local area, where microbes, including Dorea [89], Methylophilaceae [90], Ruminococcaceae [91], Fusobacterium [92], and Clostridium [92], have been reported to be significantly associated with colonic cancer or adenoma, suggesting a consistent role of these microbes in colonic health within this region. Compared to traditional classification tools that can also report the importance of OTUs in classification, the understanding of the functionality of these OTUs can only be inferred based on individual OTU classification annotations, making it difficult to obtain a more accurate understanding.…”
Section: Resultsmentioning
confidence: 99%
“…According to the AAI threshold, F. prausnitzii was included in the putative genus G12 of C2 with Gemmiger formicilis, another butyrate-producer with anti-inflammatory activity [59] . A. hadrus is another saccharolytic commensal that produces butyrate from carbohydrate metabolism and, mainly for this property, is positively associated with host health [60] . A. hadrus belonged to the genus G5 of C1 with A. caccae, the latter resulting a promising biomarker in early screening of colorectal cancer [61] .…”
Section: Discussionmentioning
confidence: 99%